OUTSOURCING IN THE STRUCTURAL REFORM JOINT STOCK COMPANY «RUSSIAN RAILWAYS» (JSCO «RZD») - Sergei Georgievich Shaginyan; Natalia Yurievna Tuhteeva (Вестник Северо-Кавказского федерального университета, 2022)
Outsourcing – the accessible tool of increase of efficiency of activity of the enterprises of a railway transportation in conditions of structural reforming Open Society " RZD". Outsourcing stage by stage also it is system it is applied practically in all departments of Open Society "RZD". Outsourcing gradually and systematically applied in almost all departments of Joint Stock Company «Russian Railways» (JSCo «RZD»). The transfer of technological processes, functions and business-processes – the next phase of outsourcing relationships. The main problems of outsourcing relationships in JSCo « » are the low validity of the decision-making on outsourcing, absence of thorough planning and specialized tools to assess the socio-economic and financial effects of their implementation, lack of methodological support for evaluation of outsourcing relationships.